Feasibility analysis of coffee shop business in Ngagel Rejo Surabaya: - Ardiansyah, Faisal Restu; Astawinetu, Erwin Dyah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The purpose of this riset is to analyze the feasibility of a coffee shop business in Ngagel Rejo, Surabaya City. The approach used in this research is a qualitative method with descriptive analysis. data collection through observation, interviews and documentation. Six informants were selected as research subjects to collect relevant data. The data will be analyzed using the calculation tools Revenue Cost Ratio (R/C), Benefit Cost Ratio (B/C) and Return On Investment (ROI). The coffee shop business in Ngagel Rejo Surabaya was studied using 6 informants. The average revenue generated by the business owner is IDR 30,235,000 / month and the average total cost is IDR 115,848,000 and the average profit is IDR 10,927,000 / month. The results of the calculation of the revenue cost ratio (R / C) of 6 coffee shop business owners have an average of 1.565. For the results of the calculation of the benefit cost ratio (B / C) of 6 coffee shop business owners has an average of 0.565 and the average return on investment (ROI) of 6 coffee shop business owners is 45%. The results of the calculation of the Revenue Cost Ratio show R / C> 1, then the calculation of the benefit cost ratio (B / C) shows B / C> 0 and the calculation of the revenue cost ratio (ROI) shows ROI> 0. Based on the data obtained with the analysis of R / C, B / C and ROI on six coffee shop business informants in Ngagel Rejo, Surabaya City is feasible to run.